Ordinary grace eaudiobook - Krueger, William Kent (Recorded Books, 2013)
From "New York Times "bestselling author William Kent Krueger comes a brilliant new novel about a young man, a small town, and murder in the summer of 1961. New Bremen, Minnesota, 1961. The Twins were playing their debut season, ice-cold root beers were at the ready at Halderson's Drug Store soda counter, and "Hot Stuff "comic books were a mainstay on every barbershop magazine rack. It was a time of innocence and hope for a country with a new, young president. But for thirteen-year-old Frank Drum it was a summer in which death assumed many forms. When tragedy unexpectedly comes to call on his family, which includes his Methodist minister father, his passionate, artistic mother, Juilliard-bound older sister, and wise-beyond-his years kid brother, Frank finds himself thrust into an adult world full of secrets, lies, adultery, and betrayal. On the surface, "Ordinary Grace" is the story of the murder of a beautiful young woman, a beloved daughter and sister. At heart, it's the story of what that tragedy does to a boy, his family, and ultimately the fabric of the small town in which he lives. Told from Frank's perspective forty years after that fateful summer, it is a moving account of a boy standing at the door of his young manhood, trying to understand a world that seems to be falling apart around him. It is an unforgettable novel about discovering the terrible price of wisdom and the enduring grace of God.